Mean-field simulations of Es-254 + Ca-48 heavy-ion reactions - Stevenson, Paul D. (Frontiers in Physics, 2022)
Einstenium-254 (Z=99,N=155), can be prepared as a target for research into nuclear reaction studies. This work presents structure and reaction calculations of Es-254 and Ca-48 (Z=20,N=28), using the Skyrme-(Time-Dependent)-Energy-Density-Functional formalism. The reaction calculations show the initial parts of the heavy-ion reaction between the nuclei which, depending on the interaction parameters, can lead to capture to a compound nucleus of element 119. For collisions with the spherical 48Ca impinging on the tip of the prolate 254Es no fusion events are found. For collisions where the calcium approaches the belly of the einsteinium, capture occurs with the compound nucleus outlasting the lifetime of the calculation, indicating a possible fusion candidate. For a sample center-of-mass collision energy of 220 MeV, slightly non-central collisions, up to an impact parameter of 1 fm, also form long-lived compound nuclei.